2020
DOI: 10.1016/j.adro.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience With Single-Isocenter Radiosurgery to Target Multiple Brain Metastases Using an Automated Treatment Planning Software: Clinical Outcomes and Optimal Target Volume Margins Strategy

Abstract: Purpose Our purpose was to assess the clinical outcomes and target positioning accuracy of frameless linear accelerator single-isocenter multiple-target (SIMT) dynamic conformal arc (DCA) stereotactic radiosurgery (SRS) for multiple brain metastases (BM). Methods and Materials Between October 2016 and September 2018, 31 consecutive patients ≥18 years old with 204 BM <3 cm in maximum size receiving SIMT DCA SRS were retrospectively evaluated. All plans were created using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
(67 reference statements)
4
29
0
Order By: Relevance
“…After an average of 12 months following up interval, very promising 1‐ and 2‐year tumor local control rates of 99 and 95% were observed. Other clinical studies have observed similar patient outcomes demonstrating SIMT‐VMAT SRS for m‐bm to be both safe and effective with high rates of tumor response 22–25 …”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…After an average of 12 months following up interval, very promising 1‐ and 2‐year tumor local control rates of 99 and 95% were observed. Other clinical studies have observed similar patient outcomes demonstrating SIMT‐VMAT SRS for m‐bm to be both safe and effective with high rates of tumor response 22–25 …”
Section: Introductionmentioning
confidence: 77%
“…41 Several recent clinical outcome studies have reported positive results of higher tumor local control rates of SIMT-VMAT treatment that do not align with the presence of these dosimetric disparities. [21][22][23][24][25] For instance Alongi et al used Varian single-isocenter VMAT in the treatment of 43 patients with m-bm and performed a clinical follow-up study within 6 months. They observed that 60% of the patients with partial or complete responses and 40% with stable disease control, though the medial overall survival had not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, irradiation of lesions <1 cc. using VMAT, or dynamic conformal arc therapy have appeared for Brain Metastases 26 , 27 and Trigeminal Neuralgia. 24 Popple et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Guckenberg showed that using a 0‐mm PTV margin on cranial lesions could result in a 40% reduction in the conformity index when intrafraction motion occurs. 25 There have been several bodies of work to investigate dosimetric impact of motion when treating larger targets (>0.52 cc) with MLC‐based VMAT, 22 , 26 , 27 but there remains a gap in the literature for investigating the dosimetric impact of treating with virtual cones. This study aims to investigate the impact of intrafraction motion when treating small cranial targets with a virtual cone.…”
Section: Introductionmentioning
confidence: 99%